Book review: Gautam Mahajan, Value Creation: The Definitive Guide for Business Leaders. Issue 2 (June 2018) - Tripathi, Shiv Shankar
Gautam Mahajan, Value Creation: The Definitive Guide for Business Leaders, 2016, New Delhi: SAGE Publications, 239 pp., ₹450 (Paperback). ISBN: 978-9351508977.